Educational Research Literacy: Philosophical Foundations and Empirical Applications - Kim Pedersen Phillips; Andreas Eriksen; Sølvi Mausethagen (Professions and Professionalism, 2023)
The paper offers a novel philosophical perspective on how research literacy should be conceptualised in the educational domain. Standard accounts of teacher research literacy consider it merely a subset of the skills of an educational researcher. Therefore, the accounts largely ignore the need to anchor or embed the mode of engagement with research in the particular demands of the professional role. By contrast, we argue that a virtue-based account of the epistemic agency involved in receiving testimony can help deliver a normatively attractive and empirically plausible account that is tailored to the role. We support the account with an original in-depth analysis of actual teacher engagement with research.